FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN STATUS GIZI BALITA DI PUSKESMAS PONCOL KOTA SEMARANG - Boediarsih Boediarsih; Wahyu Wiedy Aditantri; Dwi Kustriyanti (Jurnal Surya Muda, 2019)
Toddler nutritional status (under five years) is a picture of health regarding food consumption and use by the body at the age of under five years. Nutritional status is influenced by several factors, namely direct, indirect and fundamental. To determine the relationship between parenting, education level, mother's knowledge and family income with the nutritional status of toddlers. This type of research is correlational quantitative research with cross sectional approach. The population of children under five in the Poncol Health Center is 1312 children under five. The sampling technique in this study used proportional stratified random sampling with a sample of 89 respondents in Poncol Health Center, Semarang City. Analysis using Kolmogorov Smirnov. Factors related to nutritional status are parenting (p value = 0.411), education level (p value = 0.018), mother's knowledge (p value = 0.062), family income (p value = 0.000). There is no relationship between parenting, mother's knowledge and nutritional status. There is a relationship between education level, family income and nutritional status. Therefore it is necessary to optimize the nutritional status monitoring program for toddlers and increase community nutrition knowledge